Analysis Payment Fine Ticket Consequence The Impact of Traffic Cameras on State Finance - Rafida Khairani; Vivian Ayu Wijaya; Andry Lunoto; Franklein Franklein (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Study This own objective For know influence payment fine ticket and camera Then cross in a manner together to state finances. Approach study This uses quantitative whereas genius study uses descriptive. Source of data used namely primary and secondary. Population in research This is 5,309 violators Then recorded traffic in September 2022 in the city of Medan. Procedure for taking the sample in research This using the Slovin Technique ie 372 samples. t value count For variable Payment Fine A ticket (X 1 ) is visible that mark t count (-2.022) with level significant 0.043 0.05 means variable Payment Fine ticket influential significant to State Finance. t value counts For variable The Traffic Camera (X 2 ) is visible that mark t count (-1.856) with level significant 0.064 0.05 means variable Traffic Cameras don't have influence significant to State Finance. t value count For variable moderation between variable Payment Fine ticket with variable Traffic Camera (M) is visible that mark t count (2.425) with significance 0.015 0.05 means variable moderation between variable Payment Fine ticket with variable Traffic Camera (M) effect significant to State Finance. Calculated F value(18.333) and sig. a (0.000 a ) are located below 0.05. It means the results study can accept the hypothesis. So that can is known that variable Payment Fine Tickets and Traffic Cameras have influence significant positive in a manner simultaneous to State Finance.